A Bullous Flare of a Hyperkeratotic Affair: A Case Report. Issue 6 (November 2016) - Klimas, Natasha; West, Cameron; Tarbox, Michelle
Background: Darier's disease is an autosomal dominant genodermatosis typified by hyperkeratotic papules and plaques in a predominately seborrheic distribution. The vesiculo-bullous variant of Darier's disease is rare. Several previously reported cases have demonstrated clinical and microscopic features resembling familial benign chronic pemphigus or Hailey-Hailey disease. Objectives: The objective of this report is to describe an uncommon presentation of Darier's disease, which has been infrequently described in the literature. Methods: The authors present a case of bullous flare of long-standing Darier's disease. Conclusions: Darier's disease may assume several atypical morphologies, including vesiculo-bullous lesions.